2015
DOI: 10.1109/ted.2015.2433951
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Dual Material Junctionless Double Gate Transistor for Analog and Digital Performance

Abstract: In this paper, we report the 2-D drain current model for asymmetric dual material (DM) junctionless double gate transistor. On the basis of channel potential, transconductance and its higher order derivatives are estimated and verified with the ATLAS 3-D device simulator results. The developed model is also applicable to investigate the digital performance of the device in terms of voltage transfer characteristics of nMOS inverter circuit. The impact of the length of control gate on the analog performance has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…It has been observed that on current of proposed device is maximum and off current is minimum (1pA at channel length 120nm) which means that Ion/Ioff ratio improves compares to single material double gate junctionless transistor. Subthreshold slope of our device is minimum compare to [11] dual material double gate junctionless transistor. Threshold voltage of my proposed device and other researcher's device mentined in references is approximately same [21] [22].…”
Section: Model Verification and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been observed that on current of proposed device is maximum and off current is minimum (1pA at channel length 120nm) which means that Ion/Ioff ratio improves compares to single material double gate junctionless transistor. Subthreshold slope of our device is minimum compare to [11] dual material double gate junctionless transistor. Threshold voltage of my proposed device and other researcher's device mentined in references is approximately same [21] [22].…”
Section: Model Verification and Discussionmentioning
confidence: 86%
“…But, bulk current model for dual material double gate junctionless transistor was not found in literature. Vandana Kumari et.al demonstrated drain current model for dual material double gate junctionless transistor, but the model failed to mention the effect of channel thickness, gate oxide thickness, channel doping density and channel length on drain current [11]. In [12] current model of subthreshold region was not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of subthreshold current based on minimum channel potential (similar from [26]) can be evaluated by using the drift-diffusion equation as: This plot reflects that the IOFF significantly decreased when the channel length is increased from 20nm to 40nm. It occurred due to the barrier height being raised between the source and channel.…”
Section: Subthreshold Currentmentioning
confidence: 99%
“…Baruah et al [13] presented a study on analog circuit performance of a DMDG-JLFET with a high k-spacer. Recently, Kumari et al [10] proposed a theoretical investigation of DMDG-JLFET for analog and digital performance. Gupta et al [14], showed that a continuous increase in the threshold voltage was observed as we move down towards sub 10nm regime of the silicon film thickness.…”
Section: Introductionmentioning
confidence: 99%